Pengujian Aplikasi dengan Metode Blackbox Testing Boundary Value Analysis (Studi Kasus: Kantor Digital Politeknik Negeri Lampung) - Tri Sandhika Jaya (Politeknik Harapan Bersama, 2018)
Software testing phase is one of a critical element in determining the quality of a software. These tests include design, specification, and coding. This study aims to test the digital office software at Lampung State Polytechnic. The testing process is done to determine the level of error that occurs in the software. The test used a black box testing Boundary Value Analysis. Boundary Value Analysis is a type of test case by determine the normal value, minimum value and maximum value of the tested data. The applications resulted from this research are capable to handling data, both normal and abnormal data with a 91, 67% success rate.